Value Chain Analysis of the Broiler Industry in the Southern Sector of Ghana - Onumah, Edward Ebo; Mensah, Sarah Naa Okailey; Owusu, Prince Addey; Mensah, Amos; Otokunor, Peter Boamah (Universitas Sebelas Maret, 2023)
The livestock subsector especially broiler production plays a significant role in the livelihood and food security in Ghana. Several researchers in developing nations have employed value chain methodologies to investigate the linkages and the interactions of the various actors in the poultry sector. However, none of these studies comprehensively captured each actor’s strengths, weaknesses, opportunities and threats, as well as the governance structure and profitability of the broiler industry. This paper fills this gap by analyzing the governance structure, value addition, determinants of profitability and prospect of the broiler industry using 290 respondents (180 broiler producers, 65 distributors and 45 retailers) from the Greater Accra, Ashanti and Bono Regions of Ghana. The study adopted the scoring analytical technique, net farm income (NFI), the modified Cobb-Douglas function and the SWOT (strengths, weaknesses, opportunities, threats) matrix for the analyses. The results revealed producers as the key governors with the highest value addition and return on investment. Distributors and processors on the other hand form informal cartels to monopolize their activities to increase bargaining power. Whilst credit access, education, business training, age and feed type influenced profitability, the broiler industry is threatened by high importation of frozen chicken, high taxes, lack of capital access and high cost of operation. The study recommends that the government should pursue measures to minimize the cost of operations through input-tax exemptions and reduce the importation of chicken products. Stakeholders should invest in input supply, processing technologies and transportation facilities to boost local production for profit gains.